2004
DOI: 10.1176/appi.ajp.161.5.889
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Maternal Interleukin-8 Levels and Risk of Schizophrenia in Adult Offspring

Abstract: Using prospectively collected prenatal sera in a large and well-characterized birth cohort, the authors have documented a significant association between maternal IL-8 level during the second trimester and risk of schizophrenia spectrum disorders in the offspring. These findings provide further support for a substantive role of in utero infection or inflammation in the etiology of schizophrenia. Moreover, these results may have important implications for elucidating the mechanisms by which disrupted fetal deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
298
1
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(317 citation statements)
references
References 43 publications
10
298
1
8
Order By: Relevance
“…There is strong evidence that disruption of normal cytokine levels has a significant role as a risk factor for several neurodevelopmental defects, including schizophrenia and autism (Boulanger and Shatz, 2004;Brown et al, 2004b;Deverman and Patterson, 2009;Hsiao et al, 2013;Ponzio et al, 2007). Smith et al (2007) showed in 2007 that a single injection of the pro-inflammatory cytokine IL-6 to pregnant mice at embryonic day 12.5 lead to offspring deficits in prepulse inhibition (PPI) and latent inhibition (LI), both autism-relevant behaviors; these results were not seen following injection of the pro-inflammatory cytokines IL-1α, TNF-α, or IFN-γ.…”
Section: Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong evidence that disruption of normal cytokine levels has a significant role as a risk factor for several neurodevelopmental defects, including schizophrenia and autism (Boulanger and Shatz, 2004;Brown et al, 2004b;Deverman and Patterson, 2009;Hsiao et al, 2013;Ponzio et al, 2007). Smith et al (2007) showed in 2007 that a single injection of the pro-inflammatory cytokine IL-6 to pregnant mice at embryonic day 12.5 lead to offspring deficits in prepulse inhibition (PPI) and latent inhibition (LI), both autism-relevant behaviors; these results were not seen following injection of the pro-inflammatory cytokines IL-1α, TNF-α, or IFN-γ.…”
Section: Cytokinesmentioning
confidence: 99%
“…Inflammation and immune signaling dysregulation can strongly influence neuropsychiatric behavior beyond just ASD (Haroon et al, 2012;Meyer and Feldon, 2009), with evidence pointing toward roles in bipolar disorder and PTSD (Jones and Thomsen, 2013), and perhaps most emphatically in schizophrenia (Brown et al, 2004b;Meyer and Feldon, 2009;Michel et al, 2012;Patterson, 2009). Schizophrenia and autism share many immune similarities, including a subset of patients with an etiology based in maternal infection and immune activation (Bauman et al, 2014;Boksa, 2010;Brown et al, 2004a;Meyer et al, 2005Meyer et al, , 2007Patterson, 2009;Urakubo et al, 2001).…”
Section: Asd As An Autoimmune Disordermentioning
confidence: 99%
“…One prevalent hypothesis suggests that a common pathogenic mechanism involving increased production of cytokines and other mediators of inflammation mediates the link between prenatal infection and subsequent risk of schizophrenia. 8,9 Epidemiological support for this hypothesis, however, remains controversial, 10,11 suggesting furthermore that other mediating factors may play a role as well. 12 Exposure to traumatizing events during postnatal development is another environmental insult that has received broad recognition in the etiology of neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…13 Dysfunction of apoptosis may be involved in the pathophysiology of schizophrenia. 14 Abnormal activities of several interleukins, 15,16 including IL3, 17 have been observed in schizophrenia patients. All these lines of evidence suggest that IL3 is a plausible functional candidate for schizophrenia.…”
Section: Introductionmentioning
confidence: 99%